Software Quality. Software and Systems Quality in Distributed and Mobile Environments : 7th International Conference, SWQD 2015, Vienna, Austria, January 20-23, 2015, Proceedings - Winkler, Dietmar; Biffl, Stefan; Bergsmann, Johannes; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the scientific track of the 7th Software Quality Days Conference, SWQD 2015, held in Vienna, Austria, in January 2015. The SWQD conference offers a range of comprehensive and valuable information by presenting new ideas from the latest research papers, keynote speeches by renowned academics and industry leaders, professional lectures, exhibits, and tutorials. The four scientific full papers accepted for SWQD were each peer reviewed by three or more reviewers and selected out of 13 high-quality submissions. Further, four short papers were also presented and are included in this book. The papers are organized into topical sections on risk management and inspection, change impact analysis and systems testing, and software and systems architectures.
Part: Risk Management and Inspection -- Improving the Requirement Engineering Process with Speed-Reviews: An Industrial Case Study -- Towards a Perspective-based Usage of Mobile Failure Patterns to Focus Quality Assurance (Short Paper) -- An Exploratory Study on Risk Estimation in Risk-Based Testing Approaches (Short Paper) -- Part: Change Impact Analysis and Systems Testing -- Improving Manual Change Impact Analysis with Tool Support: A Study in an Industrial Project -- Testing of Heterogeneous Systems: An Exploratory Survey -- Part: Software and Systems Architectures -- Integrating Heterogeneous Engineering Tools and Data Models: A Roadmap for Developing Architecture Variants -- Evaluation of JavaScript Maintainability Issues and Solutions for Enterprise Application Development (Short Paper) -- Refinement-based Development of Software-controlled Safety-critical Active Medical Devices (Short Paper).
Keywords: Software engineering; Information Systems; Project management; Software Engineering; Management of Computing and Information Systems; Project Management